Prevalence of breastfeeding in a baby-friendly pediatric practice: an experience in Trieste, Italy - Mariarosa Milinco; Adriano Cattaneo; Anna Macaluso; Paola Materassi; Nicola Di Toro; Luca Ronfani (BMC, 2019)
Abstract Background In a pediatric practice in Italy, actions were undertaken to apply the recommendations for a breastfeeding-friendly physician's office and to promote the adoption of a semi-reclined or laid-back maternal position in breastfeeding. The aim of this study is to evaluate the effect of the actions implemented, in terms of prevalence of exclusive breastfeeding. Methods A historical cohort study was carried out using administrative data routinely collected. All women who gave birth in 2016 and registered their newborns with the pediatric practice were included, only mothers of preterm newborns < 30 weeks gestational age were excluded. The main actions undertaken were: employment of a breastfeeding peer supporter; ensuring unlimited daily access in case of breastfeeding difficulties; provision of individual support to breastfeeding mothers in a dedicated room and advice on the laid-back position; scheduling of weekly meetings of small groups for breastfeeding support. Each infant was followed up for five months. The main study outcomes were duration of exclusive breastfeeding (only breast milk and no other liquids or solids, except for drops of syrups with nutritional supplements or medicines) and prevalence at five months. Results A total of 265 newborn infants with a gestational age greater than 30 weeks were registered with the pediatric practice during the study period, about 18% of all infants born in Trieste in that period. Complete data were available for 252 of these (95.1%). The rate of exclusive breastfeeding at five months of age was higher than the one reported for the whole infant population of Trieste and of the Friuli Venezia Giulia Region (62.3% vs. 42.9% vs. 30.3%) in the same period. Conclusions The implementation of breastfeeding-friendly pediatric practice and the application of laid-back breastfeeding may improve the rate and duration of exclusive breastfeeding.